UMP bags 10 medals and The Best Award for Consumer Electronics - Dina Diyana, Rastam Tan (2020)
A highly efficient light-emitting diode (LED) system known as MP-Rediac LED Stick was awarded a gold medal and special award “The Best Award for Consumer Electronics” in the Malaysia Technology Expo (MTE) 2020 which was held for three days from 20 February 2020 in the Putra World Trade Center (PWTC), Kuala Lumpur.